2011
DOI: 10.1021/jf1041933
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Compounds Responsible for Antioxidant Capacity of Euryale ferox Seeds

Abstract: Euryale ferox seed is consumed medicinally or for food in China. The present study revealed it to contain significant antioxidant activity, which may be associated with its medical applications as a proteinuria inhibitor of diabetic nephropathy. This study resulted in the identification of 3 new sesquineolignans, named euryalins A-C (1-3), and 16 known compounds, which were all first isolated from this plant apart from 5,7,4-trihydroxy-flavanone. The antioxidant potential of the partial isolates was evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 17 publications
1
38
0
Order By: Relevance
“…Other herbs in the formulation include euryale ferox, alisma orientale and rhodiola rosea. Both euryale ferox and alisma orientale have anti-oxidative activity [15,16] while a component of rhodiola rosea (salidroside) could inhibit inflammatory cytokines production such as tumor necrosis factor alpha and interleukin-6 [17]. Therefore, Yishen capsule has anti-oxidative and anti-inflammatory function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other herbs in the formulation include euryale ferox, alisma orientale and rhodiola rosea. Both euryale ferox and alisma orientale have anti-oxidative activity [15,16] while a component of rhodiola rosea (salidroside) could inhibit inflammatory cytokines production such as tumor necrosis factor alpha and interleukin-6 [17]. Therefore, Yishen capsule has anti-oxidative and anti-inflammatory function.…”
Section: Discussionmentioning
confidence: 99%
“…In addition astragalus membranaceus has been shown to improve patients’ proteinuria with idiopathic membranous nephropathy [13,14]. Euryale ferox and alisma orientale also have antioxidative activity [15,16]. Salidroside from rhodiola rosea has anti-inflammatory activity by inhibiting production of tumor necrosis factor alpha and interleukin-6 [17].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, high contents of gallic acid were detected in the three EFSS extracts; however, rutin, another major component in the EFSS extracts, was not mentioned in the report of Song et al . (). Based on these results, I concluded that rutin is present in seed shells but not in seed kernels.…”
Section: Resultsmentioning
confidence: 97%
“…However, Song et al . () isolated and identified 19 compounds, including gallic acid and its derivatives, in E . ferox seed kernels, and all the identified molecules contained a phenolic hydroxyl group.…”
Section: Resultsmentioning
confidence: 99%
“…. Furthermore, syringaresinol and its glucosides showed strong α,α-dipenyl-β-picrylhydrazyl (DPPH) radical-scavenging activity 13,14) . Free radicals are directly implicated in the development of cancer by their ability to damage the DNA in a cell's nucleus and weaken the immune system, which normally destroys cancer cells or prevents them from reproducing.…”
Section: Resultsmentioning
confidence: 99%